Pain in adults with cerebral palsy after single-event multilevel surgery - Götze, Marco; Geisbüsch, Andreas; Thielen, Mirjam; Döderlein, Leonhard; Wolf, Sebastian Immanuel; Dreher, Thomas; Putz, Cornelia (American journal of physical medicine & rehabilitation, 2022)
Objective - The aim of the investigation was to assess the contribution of pain to functional, social, and health-related quality-of-life outcomes in adults with cerebral palsy. - Design - This monocentric, prospective study included long-term data for ambulant adults with cerebral palsy and at levels I-III in the Gross Motor Function Classification System who had received orthopedic multilevel surgery in adulthood and in whom preoperative and postoperative three-dimensional gait analysis was conducted, including the Gait Profile Score. A questionnaire including the Visual Analog Scale, Oswestry Disability Index, and European Quality of Life 5 Dimensions 3 Level was analyzed. - Results - Twenty-four adults at a mean age of 38.0 yrs were included. Sixteen patients (66.7%) indicated that they experienced pain and 10 patients (41.7%) had pain for more than 6 mos. Overall, 13 patients (54%) experienced both pain and anxiety. There was no correlation of the Gait Profile Score with pain, Gross Motor Function Classification System, and Oswestry Disability Index. The Oswestry Disability Index showed a positive correlation with the Gross Motor Function Classification System (r = 0.39, P = 0.05) and pain (r = 0.57, P = 0.004). - Conclusions - Pain and anxiety represent relevant comorbidities in adults with cerebral palsy. The occurrence of pain correlates with the Oswestry Disability Index and is higher than in children with cerebral palsy.